2022
DOI: 10.1007/s13202-022-01453-w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of CO2 injectivity impairment in sandstone due to salt precipitation and fines migration

Abstract: Re-injection of carbon dioxide (CO2) in deep saline formation is a promising approach to allow high CO2 gas fields to be developed in the Southeast Asia region. However, the solubility between CO2 and formation water could cause injectivity problems such as salt precipitation and fines migration. Although both mechanisms have been widely investigated individually, the coupled effect of both mechanisms has not been studied experimentally. This research work aims to quantify CO2 injectivity alteration induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…They have shown that the CO 2 –brine–rock interaction can happen in both zones of water and gas because, during the reaction, water can evaporate to the steam phase, while CO 2 reacts with the brine water, resulting in carbonic acid. Similarly, the study revealed that the CO 2 –brine–rock interaction leads to formation damage because the reaction of the rock mineral may dissolute and form free particles that can be transported and fill the pore spaces along the pass of fluid flow, leading to a severe reduction of permeability. , .…”
Section: Concept Of Formation Damage During Co2 Sequestrationmentioning
confidence: 99%
See 3 more Smart Citations
“…They have shown that the CO 2 –brine–rock interaction can happen in both zones of water and gas because, during the reaction, water can evaporate to the steam phase, while CO 2 reacts with the brine water, resulting in carbonic acid. Similarly, the study revealed that the CO 2 –brine–rock interaction leads to formation damage because the reaction of the rock mineral may dissolute and form free particles that can be transported and fill the pore spaces along the pass of fluid flow, leading to a severe reduction of permeability. , .…”
Section: Concept Of Formation Damage During Co2 Sequestrationmentioning
confidence: 99%
“…According to Sbai and Azaroual, several mechanisms have contributed to the formation damage, such as active mineral precipitation and trapped particles, causing blocking/plugging and bridging processes, particularly in porous environments. Also, clogging of the suspended particles at the pore throats during an unprecedented flow rate of CO 2 storage could result in restriction of production and a loss in permeability surrounding the injector zone. , Research by Mohamed and Nasr-El-Din showed the reduction of CO 2 injectivity in carbonate rock as a result of the formation damage resulting from the precipitation of carbonate minerals and sulfate scales. Usually, sodium sulfate in brine water causes formation damage as a result of the precipitation of calcium sulfate .…”
Section: Concept Of Formation Damage During Co2 Sequestrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous researchers have discussed CO 2 storage in geological formations with various theories, and simulation models. They outlined that CCS is a safe technology to meet the climate targets as stated by IPCC, organizations, research, and different governments. In addition to the many advantages of CCS, this technique faces many difficulties, such as high operational costs (as described by Moghanloo et al and Fawad and Mondol), proper handling to prevent compromise with wellbore integrity, public acceptance by some countries, and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%